Sustainable Market Environment and Consumer Confidence in Food Safety in China After COVID-19: Urban Consumer Perspectives - Abbas, Hasnain; Ullah, Hafeez; Gong, Xi; Jiang, Mengyin; Faiz, Narmeen; Zhao, Lindu (The Economics and Finance Letters, 2022)
Previously, several food safety incidents have lowered Chinese consumer confidence regarding the purchase of meat and domestically-produced infant formulas (DIF). Recently, the COVID-19 pandemic was caused by a food safety issue, and it is, therefore, important to investigate sustainable consumer confidence and its influence on consumption behavior by first estimating consumer confidence in meat and DIF products. The purpose of this study is thus to estimate the sustainable market environment and Chinese consumer confidence behavior post-COVID-19 regarding the purchase of meat and DIF products by applying a choice experiment. An online survey was conducted with 704 consumers residing in Nanjing. The survey obtained information on the features of meat and DIF products that affected consumer purchase consideration and determined the perceived estimated value of the product (price 15.24%, quality certification 31.57%, organic 23.69%, traceability 18.51%). These findings provide insight into consumer perceived premium pay behavior concerning the value estimation of product features according to the market environment (price 191.6 CNY, quality certification 285.3 CNY, organic product 189.1 CNY, and traceability 143.7 CNY). Chinese consumers’ low confidence in the safety of meat and DIF products appears less sustainable. Quality certification is the product feature that is most valued, followed by organic origin and production-to-consumption traceability. Apart from these, price is seen as an indication of high quality by consumers with low confidence, which results in a positive image of DIF products. In addition, consumer preferences for production-to-consumption traceability are highly affected by consumer confidence.